ACCOUNTING SERVICES CATERING AND UNIFORMS IN THE HOTEL INDUSTRY - E. Shapoval; G. Gogolishvili (Вестник университета, 2016)
This article explores the issues keeping the catering services and uniforms to companies hospitality sector. Currently, the scope of public power, as one of the fastest growing industries in the Russian service sector has its own characteristics, as well as accounting and uniforms, subject trebovany legislation on consumer protection, in bookkeeping and taxation, the organization of economic activity, taking into account the income and expenses at the enterprises of hotel type. When accounting for these services is very important to consider all the details related to the state regulation in this sphere.